The Effect of Accounting Information System Quality and Service Quality on Accounting Information System User Satisfaction in Local Government Institutions - Yesa Selfia; Gun Gunawan Rachman; Ayi Astuti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to examine the effect of Accounting Information System Quality and Service Quality on Accounting Information System User Satisfaction in local government institutions. The research adopts a quantitative approach, utilizing survey data collected through questionnaires from 38 respondents selected using simple random sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Accounting Information System Quality and Service Quality have a positive and significant effect on Accounting Information System User Satisfaction, with a moderate level of influence. The model exhibits strong explanatory power, as indicated by the coefficient of determinations (R²) of 0,775, suggesting that these variables explain a substantial proportion of user satisfaction. This study provides empirical evidence of the importance of Accounting Information System Quality and Service Quality in enhancing Accounting Information System User Satisfaction, and improving these aspects is expected to contribute to better system performance and user outcomes, particularly in public sector organizations.